Sex differences in injury rates in team-sport athletes: a systematic review and meta-regression analysis - Zech, Astrid; Hollander, Karsten; Junge, Astrid; Steib, Simon; Groll, Andreas; Heiner, Jonas; Nowak, Florian; Pfeiffer, Daniel; Rahlf, Anna Lina (Journal of sport and health science, 2022)
Background - Team-sport players have a particularly high injury risk. Although female sex is considered a risk factor, it is still unknown whether female and male team-sport players, in fact, differ in their injury rates. We aimed to compare injury rates between female and male players by systematically reviewing and meta-analyzing injury surveillance studies of both sexes in order to evaluate sex-specific differences in team-sport injuries. - Methods - Studies that prospectively collected injury data for high-level female and male players (age ≥16 years) in basketball, field hockey, football (soccer), handball, rugby (union and sevens), and volleyball were included. Two reviewers (AZ and ALR) independently assessed study quality and extracted data for overall, match, training, and severe injuries (>28 days’ time loss) as well as data regarding injury locations and types. Incidence rate ratios (IRRs) were pooled in a meta-analysis, and meta-regression analysis was performed when 10 or more studies were available. - Results - Of 20 studies, 9 studies reported injury data from football, 3 studies from rugby, 3 studies from handball, 1 study from basketball, 1 study from field hockey, 2 studies from volleyball, and 1 study from basketball and field hockey. For overall injuries, the pooled IRR = 0.86 (95% confidence interval (95%CI): 0.76−0.98) indicated significantly more injuries in male than in female players. For injury location, the pooled IRR showed higher injury rates in male athletes than in female athletes for upper extremity, hip/groin, thigh, and foot injuries. Female players had a significantly higher rate of anterior cruciate ligament injuries (IRR=2.15, 95%CI: 1.27−3.62) than male players. No significant sex-specific differences in IRR were found for match, training, severe injuries, concussions, or ankle sprains. - Conclusion - Our meta-analysis provides evidence for sex-specific differences in the injury rates in team sports. Further epidemiological studies including both sexes in sports other than football are needed in order to strengthen the evidence.